Critical review of type specimens deposited in the Malacological collection of the biological institute/Ufrj, Rio de Janeiro, Brazil - Oliveira, Cléo Dilnei De Castro; Pimenta, Alexandre Dias; Figueira, Raquel Medeiros Andrade; Absalão, Ricardo Silva (Zootaxa, 2018)
The Malacological Collection of the Biological Institute of Federal University of Rio de Janeiro figures as an important repository of specimens, containing c.a. 21,000 lots, most of them collected at deep sea of southeast Brazil. A critical review of literature and types deposited in this collection revealed the existence of 191 lots containing type specimens (23 holotypes and 168 paratypes), corresponding to 129 nominal species divided in three classes: Gastropoda (109 names, subdivided in 62 Caenogastropoda; 32 Heterobranchia and 15 Vetigastropoda), Bivalvia (17 names subdivided in 10 Protobranchia; 6 Heterodonta and 1 Pteriomorphia), and Scaphopoda (3 names). For each species, an updated list of data is provided, including the collecting location (revised or corrected, when necessary), number of specimens actually present (i.e., physically found in the collection), nomenclatural acts (if needed) and any other specific issue concerning particular species. It is beyond the scope of this study to discuss classifications or promote subjective judgment on taxonomy at any level for names treated here.